2016
DOI: 10.4491/eer.2016.061
|View full text |Cite
|
Sign up to set email alerts
|

Electric power generation from treatment of food waste leachate using microbial fuel cell

Abstract: The volume of the air-diffusion cathode MFC was 234 mL (6.5 cm × 6 cm × 6 cm), with an effective volume of 200 mL (Fig. 1).Environ. Eng. Res. 2017; 22(2): 157-161 pISSN 1226-1025 https://doi. ABSTRACTSimultaneous treatment of food waste leachate and power generation was investigated in an air-cathode microbial fuel cell. A TCOD removal efficiency of 95.4 ± 0.3% was achieved for an initial COD concentration of 2,860 mg/L. Maximum power density ranged was maximized at 1.86 W/m 3 , when COD concentration varied b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 20 publications
0
2
0
1
Order By: Relevance
“…[17][18][19]. Among MESs, MFCs are the system that generates electricity by degrading organic matter in wastewater using a microbial catalyst in the anode [20][21][22][23][24][25][26][27][28][29][30]. This technology has the potential to prevent direct fuel combustion and convert the chemical energy of organic waste into bioelectricity [31].…”
Section: Introductionmentioning
confidence: 99%
“…[17][18][19]. Among MESs, MFCs are the system that generates electricity by degrading organic matter in wastewater using a microbial catalyst in the anode [20][21][22][23][24][25][26][27][28][29][30]. This technology has the potential to prevent direct fuel combustion and convert the chemical energy of organic waste into bioelectricity [31].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, bioremediation processes are more cost-effective, eco-friendly and thorough tactics to remove CNPs from waste water. Recent studies have shown that bioelectrochemical systems (BES) (including microbial fuel cells (MFC) [16][17][18][19], microbial electrolysis cells (MEC) [20].). There is the ability to remove refractory pollutants in water of those BES.…”
Section: Introductionmentioning
confidence: 99%
“…44 은 하폐수의 유기물을 산화하여 전자(e -)와 양성자(H + )를 형성 한다. [24][25][26][27][28][29] 이는 MFC의 산화전극과 동일한 기작이지만 방출된 전자는 미생물연료전지 (Microbial fuel cell, MFC)와 같이 전기 를 생성하지 않고 30) , 환원전극 표면에서 양성자와 결합하여 최종 생성물로 수소가스를 생성한다. 산화전극과 환원전극에서 발생하는 전기화학적 반응은 다 음 식(Eq.…”
unclassified